The Role of Blue Economy in Enhancing Economic Growth - Danio, Andre; Saputro, Eko Guntur; Suwito, Suwito (PPSDP International Journal of Education, 2025)
This study investigates the role of the Blue Economy in fostering economic growth in Indonesia, focusing on the sustainable management of marine resources. Marine biotechnology presents immense potential for innovation and economic growth through the development of new products and technologies. Environmentally friendly maritime transportation reduces the environmental impact of shipping, supporting broader sustainability goals. This study underscores the importance of integrating sustainable practices across various marine sectors to achieve a balance between economic growth and environmental conservation. The novelty of the study lies in its comprehensive analysis of the Blue Economy’s diverse sectors and their collective impact on Indonesia’s economy. The findings contribute to the understanding of the Blue Economy’s potential and provide valuable insights for policymakers to formulate strategies that promote sustainable development in marine sectors, ultimately benefiting the economy, society, and the environment.